FINANCIAL ANALYST COVERAGE AND RISK-ADJUSTED RETURNS - Rahadi, Febri (LPPM Universitas Muhammadiyah Sumatera Barat, 2016)
This study examines the relationship between risk adjusted stock returns and analysts following. Jensen’s Alpha was used to calculate risk adjusted stock returns. I analyze data on analysts following for sample firm from Institutional Broker Estimate System (I/B/E/S) Detail History tape. The data set covers the period from 1982 to 2012 and found that firm with better risk adjusted stock returns will attract more analysts to provide research reports for investors. The result implied that risk adjusted returns contained more firm’s information for financial analysts. Firms with better information will attract more analysts to follow since the analyst will save more time and effort in gathering information for their own purpose. Keywords: Risk-Adjusted Stock Returns, Jensen’s Alpha, Financial Analysts, Analyst Following